Seismic performance limit of nuclear power plant piping system with seismic isolation system considering measurement points: Low-cycle fatigue life. (December 2021) - Kim, Sung-Wan; Jeon, Bub-Gyu; Hahm, Dae-Gi; Kim, Min-Kyu
Highlights: In order to quantitatively define seismic performance limits regarding leakage, actual failure, caused by low-cycle fatigue, in-plane cyclic loading tests were performed. Leakage lines were examined for a thin-walled steel pipe elbow considering measurement points. Low-cycle fatigue curves were presented for a thin-walled steel pipe elbow considering measurement points. Abstract: This paper presents the first part of a two-part investigation on the seismic performance limits of nuclear power plant piping systems with seismic isolation systems considering the measurement points and proposes a scheme for low-cycle fatigue life. This part of the study focuses on pipe elbows, which are components vulnerable to seismic loads in crossover piping systems connecting structures with and without seismic isolation systems in nuclear power plants. The low-cycle fatigue life, which is the seismic performance limit of the pipe elbow, was determined by considering the cyclic loading of the low-frequency characteristics caused by the seismic isolation system. Three-inch test specimens of SCH40, which are typical standards for nuclear power plant piping systems, are fabricated herein consisting of a pipe elbow and straight pipes. In the test specimens, the pipe elbow where the load is concentrated and the lengths of the straight pipes that are connected to the elbow may differ from those in field conditions. Therefore, their effects on the seismic performance limit were analyzed using the relationship between the moment and deformation angle. Cyclic loadings were performed at varying amounts of a constant amplitude, and an imaging system was used to measure the moments and deformation angles. The deformed shapes of the test specimens caused by external forces were compared for each measurement point, and the leakage lines and low-cycle fatigue curves were presented using the relationship between the moment and relative deformation angle.